Cancer-associated non-bacterial thrombotic endocarditis. Issue 213 (May 2022) - Itzhaki Ben Zadok, Osnat; Spectre, Galia; Leader, Avi
Abstract: This paper reviews the current evidence on the pathogenesis, clinical manifestations, diagnosis and management of cancer-associated non-bacterial thrombotic endocarditis (NBTE). NBTE is an underdiagnosed condition characterized by sterile valvular vegetations composed of platelets and fibrin which are susceptible to systemic embolization. Cancer is a leading cause of NBTE and should be excluded in NBTE cases without a clear etiology. Malignancies most frequently associated with NBTE are mucin-releasing adenocarcinomas of the lung, ovary, biliary system, pancreas, breast and stomach. NBTE carries a high risk of arterial thromboembolism, while cardiac valvular dysfunction is much less frequent. NBTE appears to be an important underdiagnosed cause of cancer-associated embolic stroke of undetermined source. Characteristics associated with cancer-associated NBTE include elevated D-dimer, visceral infarcts, cerebral infarcts in multiple vascular territories, transcranial doppler microembolic signals, disseminated cancer and adenocarcinoma histology. Transesophageal echocardiography is the diagnostic test of choice, and all suspected cases should be evaluated for the presence of elevated D-dimers and disseminated intravascular coagulation. Long-term anticoagulation with low molecular weight heparin should be strongly considered, and surgical intervention is usually not needed. Underlying cancer must be diagnosed swiftly (if previously undiagnosed) and anti-cancer treatment should be initiated as soon as possible. The paucity of data regarding all aspects of NBTE, and the severe clinical consequences of untreated NBTE, are an urgent call for future research. Highlights: Cancer is common in non-bacterial thrombotic endocarditis (NBTE) and should be excluded. Undiagnosed NBTE is an important cause of cryptogenic cancer-associated embolic stroke. Transesophageal echocardiography is the gold standard for diagnosing NBTE. NBTE carries a high risk of arterial thromboembolism, including recurrent embolism. Long-term anticoagulation with low molecular weight heparin should be strongly considered.